SIMBOL-SIMBOL YANG DIGUNAKAN PADA GROUP BAND HEAVY METAL: SEBUAH ANALISIS SEMIOTIK - Pietersz, Erwin Juliano (JURNAL ELEKTRONIK FAKULTAS SASTRA UNIVERSITAS SAM RATULANGI)
ABSTRACT Semiotics is a study about signs. Symbols is a part of sign which can be found in some different forms such as verbal or nonverbal, written or unwritten. They can be anything that convey meaning such as words on papers, pictures, drawings, and gestures. In this research, the writer takes the symbols used by heavy metal bands as the object of research. The purpose of the research is to identify and analyze the symbols used by the heavy metal bands as one of the sign systems from the semiotics point of view. The aspects of research which are related to the sign systems proposed by Peirce are icon, index and symbol. Symbols also can be found in some musical genres for example the heavy metal music. In this category, symbols are used by the heavy metal bands as their own identity.The collected data about semiotics and Peirce theory of signs were collected from some books of semiotics while the data about the heavy metal bands and their symbols are collected from the websites. All the collected data are analyzed based on Peirce theory of signs, and the method used is descriptive method. The results of this research show that there are four main subgenres of heavy metal and each genre has its own form of the symbols. The form of the symbols illustrate the musical genre that they play and also representate the lyrical themes of their songs each other. Â Keywords: Semiotics, Symbols, Heavy Metal, Symbols of the Heavy Metal bands